In vitro Regeneration of Clematis Plants in the Nikita Botanical Garden via Somatic Embryogenesis and Organogenesis - Mitrofanova, Irina; Ivanova, Natalia; Kuzmina, Tatyana; Mitrofanova, Olga; Zubkova, Natalya (Frontiers in Plant Science, 2021)
The effect of growth regulators, namely 6-benzylaminopurine (BAP) and thidiazuron (TDZ), on morphogenic capacity of 13 cultivars of clematis plants, in terms of their morphological structure formation, shoot regeneration and somatic embryo development, are presented. The clematis cultivars ‘Alpinist’, ‘Ay-Nor’, ‘Bal Tsvetov’, ‘Crimson Star’, ‘Crystal Fountain’’, Kosmicheskaya Melodiya’, ‘Lesnaya Opera’, ‘Madame Julia Correvon’, ‘Nevesta’, ‘Nikitsky Rosovyi’, ‘Nikolay Rubtsov’, ‘Serenada Kryma’, ‘Vechniy Zov’, were all taken in collection plots of the Nikita Botanical Gardens – National Scientific Center for use in study. After explant sterilization, 1-cm long segments with a single node were introduced to an in vitro culture. The explants were established on the basal MS medium supplemented with BAP (2.20–8.90 μM) and 0.049 μM NAA or TDZ (3.0; 6.0, and 9.0 μM) with 30 g/L sucrose and 9 g/L agar. Medium with 0.89 μM BAP served as the control. Culture vessels and test tubes with the explants were maintained in a plant growth chambers at 16-h photoperiod, a light intensity 37.5 μmol m-2s-1, a temperature of 24 ± 1°C. Histological analysis demonstrated that adventitious buds and somatic embryos formation in studied clematis cultivars occurred at numerous areas of active meristematic cells zones. It was determined that maximum adventitious microshoot regeneration without any morphological abnormalities formed on the media supplemented with BAP or TDZ. 4.40 μM BAP or 6.0 μM TDZ were optimal cytokinin concentrations for micropropagation. The explants of ‘Alpinist’, ‘Ay-Nor’, ‘Crimson Star’, ‘Crystal Fountain’, ‘Nevesta’, ‘Serenada Kryma’ cultivars displayed high morphogenetic capacity under in vitro culturing. The main role of genotype was demonstrated. Light intensity 37.5 μmol m-2s-1 stimulated a higher number somatic embryos formation and temperature of 26°C affected somatic embryos development. 2.20 μM BAP with 0.09 μM IBA affected the high number somatic embryos formation for eight cultivars. Secondary somatic embryogenesis by the same concentration of BAP was induced. The frequency of secondary somatic embryogenesis was higher in‘Crystal Fountain’ (100%), ‘Crimson Star’ (100%), ‘Nevesta’ (97%) and ‘Ay-Nor’ (92%) cultivars. Based on these results, the methodology for direct somatic embryogenesis and organogenesis of studied clematis cultivars has been developed.